Towards the Achievement of SDGs with Zakat: - Suhail Ahmad; Sahibzada Ghiasul Haq (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
The World Bank Group (WBG) has a contractual relationship with the United Nations (UN), which has a history of its founding, and through that relationship acts to form an association that supports member states and results in development. Contributes Effectively, over the years, the WBG has collaborated with the United Nations in virtually all regions and sectors to protect the different mandates of each organization, and its commitment deepens as the Millennium Development Goals (MDGs) are adopted and now with Sustainable Development Goals (SDGs). Toady poverty is a challenge for the World and a lot of individuals living below the poverty line. According to World Bank billions of individuals live in extreme poverty i.e. below 1.9 per day. Around one billion people around the World live in extreme poverty, The World Bank vision 2030, that to eradicate poverty across the globe and that’s why they set SDGs with UN for the betterment of the community and individuals live equally and have access to their basic necessities of life. The United nation’s 17 SDGs are a joint venture for the better and more sustainable future of our planet and its inhabitants. The UN & World Bank placed poverty eradication is goal number one among 17 sustainable development goals and we can see the importance of the poverty eradication among SDGs goals. Towards achieving of SDGs number I, this study takes the Khushal Garh village of the Malakand District of Khyber Pakhtunkhwa Pakistan as a case study, and sees that how the efforts are made for the attainment of SDGs of WBG and UN, and the people are getting better from their previous life style. This paper also highlights some factors which cause poverty in the country. This model can also be used by other countries in their respective context and will lead the eradication of poverty in terms of health care and educational facilities, which results the socioeconomic development of a community.